Leucoagaricus fragilis sp. nov. (Agaricaceae) from Punjab, Pakistan - Asif, Muhammad; Niazi, Abdul Rehman; Izhar, Aiman; Khalid, Abdul Nasir; Bashir, Hira (Phytotaxa, 2021)
A novel species, Leucoagaricus fragilis, is described from the vicinity of the Cholistan desert, Punjab, Pakistan. The taxon is characterized by white, fragile basidiomata with a light brown, umbonate disk, a radially fibrillose pileus surface rarely splitting radially, pinkish brown lamellae at maturity, a white, bent stipe that stains yellowish upon handling, an inferior annulus, sub-globose to ellipsoid basidiospores, broadly clavate to abundantly sphaeropedunculate cheilocystidia, and cylindrical pileipellis hyphae intermixed with broader clavate elements with rounded ends. Morpho-anatomical and molecular phylogenetic analyses of nrITS and nrLSU datasets confirmed a new taxon in L. sect. Piloselli. A key to the known species of Leucoagaricus in Pakistan is also provided.